Pain management strategies for acute abdominal pain in the emergency department: a study from the Al-Hilla Teaching Hospital (Iraq) - Al-Saigh, Ali Jalil; Abdalwahd, Noor; Kadhum, Rusul W.; Al-Saigh, Rafal J.; Al-Humadi, Sally H.; Alsaigh, Noor Jalil (Pharmakeftiki, 2025)
Acute abdominal pain is a frequent cause of emergency department (ED) visits, yet the management of pain in patients with acute abdominal pain remains controversial. Concerns about masking symptoms and delaying diagnosis have traditionally led to the withholding of analgesics prior to diagnosis. However, recent evidence suggests that early pain management does not compromise diagnostic accuracy or outcomes. This study evaluates the demographic and clinical characteristics of 97 patients presenting with acute abdominal pain at the Al-Hilla Teaching Hospital in Babylon, Iraq, from June 2023 to September 2023. The study focuses on their medication intake and pain management strategies, highlighting the effectiveness of a multimodal approach, including the use of esomeprazole, ketorolac, hyoscine butylbromide, ondansetron, and budesonide, in alleviating pain and associated symptoms. The results show that majority of the patients (90.7%) presented to the ED within 6 h of pain onset. The most frequently administered medications were esomeprazole (95.8%), ketorolac (70.1%), and antibiotics (64.9%). Pain subsided within 30–49 min in 60.8% of patients, demonstrating the effectiveness of early analgesia. The study supports the safe and timely administration of analgesics in the ED, challenging traditional practices and emphasizing the need for updated guidelines in order to improve patient care in emergency settings.